1995
DOI: 10.1042/bj3120281
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis by the large subunit of the second β-galactosidase of Escherichia coli in the absence of the small subunit

Abstract: Plasmids containing the ebgAo and ebgAa genes of Escherichia coli under the control of the lac repressor and promoter have been constructed and inserted into Salmonella typhimurium CH3. This system expresses the large subunit of the ebgo and ebga beta-galactosidase in high yield (20-60% of total protein). The large subunits have been purified to homogeneity. As isolated they are tetramers of significant catalytic activity; the N-terminal amino acid residue is Met, but it is not formylated. The kcat. values for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…The inactivation rates in the absence of the small subunit in the two cases examined (ebg o and ebg a ) show modest decreases over the inactivation rates of the corresponding intact enzyme. This is expected in the light of the evidence that we presented [5] that indicated that the main function of the small subunit was to alter the active-site conformation such that application of electrophilic catalysis was more effective. (Given the extensive homology between lacZ and ebg enzymes, it is reasonable to assume that a single active site of the ebg enzyme, like that of the lacZ enzyme [1], is composed of residues from two subunits.…”
Section: Figure 3 Time-dependent Inactivation Of Ebg Ab At Ph 7n5 Andmentioning
confidence: 73%
See 2 more Smart Citations
“…The inactivation rates in the absence of the small subunit in the two cases examined (ebg o and ebg a ) show modest decreases over the inactivation rates of the corresponding intact enzyme. This is expected in the light of the evidence that we presented [5] that indicated that the main function of the small subunit was to alter the active-site conformation such that application of electrophilic catalysis was more effective. (Given the extensive homology between lacZ and ebg enzymes, it is reasonable to assume that a single active site of the ebg enzyme, like that of the lacZ enzyme [1], is composed of residues from two subunits.…”
Section: Figure 3 Time-dependent Inactivation Of Ebg Ab At Ph 7n5 Andmentioning
confidence: 73%
“…The various ebg enzymes were purified from the sources and by the procedures already described for ebg o , ebg a , ebg b , ebg ab [3,7], ebg abcd and ebg abcde [17], and for the large (α) subunits of ebg a and ebg o [5]. ψebg a and ψebg b are versions of the enzyme with the PCR-induced Leu-9 His mutation, as described previously [5]. Release of 2,4-dinitrophenol from the inactivator by high concentrations of enzyme was monitored at 400 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…). Finally, group VII is characterized by the presence of EbgC, a fourth E. coli paralog that has been described as a component of an enzyme (Ebg) with marginal β‐galactosidase activity . Nonconservative substitutions are observed in EbgC at the metal‐binding site (Fig ), suggesting loss of catalytic activity in this divergent member of the DUF386 family.…”
Section: Similarity With Other Structuresmentioning
confidence: 99%
“…Michael Sinnott and his colleagues have studied the mechanisms of catalysis, including the transition state structure and constructed free energy profiles, for the wild‐type enzyme (Ebg 0 ), Class I enzyme (Ebg a ), Class II enzyme (Ebg b ), two different Class IV enzymes (Ebg ab and Ebg abcd ) and the Class V enzyme (Ebg abcde ) [17–23].…”
Section: Analysis Of Catalysismentioning
confidence: 99%